A comparison of analgesic effect of intraarticular ropivacine with bupivacaine following knee avthroscopy - (:unkn) unknown (My University, 2000)
The aim of this study was to compare the analgesic effect of intraarticular ropivacaine with bupivacaine following knee arthroscopy. 30 patients, aged between 20-60 years and undergoing elective knee arthroscopy were enrolled into the study protocol. A standardized general anesthesia including 5 mg/kg thiopental-sodium, 0.1 mg/kg vecuronium-bromide i.v. and 1 MAC sevoflurane with 66 % N2O in oxygen was administered to all patients. At the end of surgery the patients were randomly assigned into two groups (n=15). Group I received 20 ml 0.75 % ropivacaine and group II received 20 ml 0.5 % bupivacaine intraarticularly. Pain scores with Visual Analogue Scale at 1., 2., 4., 6., 12., 24. hours postoperatively, time to the first analgesic requirement and side effects were recorded. There were no significant difference in the postoperative pain scores of the patients between groups. The first analgesic requirement times were not statistically different (391.66 ± 81.7 rain in group I and 444.16 ± 64.8 rain in group II). 10 patients in group I (66 %) and 5 patients in group II (33 %) needed no additional analgesic during 24 hours (p>0.05). No side effect was observed in any patient. We concluded that intraarticular 20 ml 0.75 % ropivacaine provides effective analgesia comparable to that provided by 20 ml 0.5 % bupivacaine.
Keywords: Bupivacaine; Intraarticular analgesia; Ropivacaine